PENERAPAN MODEL PEMBELAJARAN KONSTRUKTIVISME BERBANTUAN CONCEPT MAP UNTUK MENINGKATKAN HASIL BELAJAR KIMIA PADA SISWA SMA - Novia, Teti Rizqi; Kusumo, Ersanghono (Jurnal Inovasi Pendidikan Kimia, 2013)
This research aimed to improve learning outcomes of student in an high school on academic year 2011/2012. Subject of this class action research is the class X-3 as many as 34 students at stoichiometry material. This research consisted of three cycles, each cycle consisted of four stages: planning, action, observation and reflection. The research data obtained by test and observation methods. The result showed that average cognitive learning outcome of student in cycle I is 78.53 with 76.47% of completeness classical, cycle II is 80.88 with 82.35% classical completeness, and cycle III is 87.06 with 88.24% completeness classical. The average affective learning outcome of student in cycles I, II, and III are 74.36, 78.77, and 86.22. While average psychomotoric learning  outcome of students in the cycle I is 70.59, cycle II is 76.66 and cycle III is 86.86. From these results, it can be concluded that the application of constructivism learning model assisted by concept map can improve student learning outcomes.